2013
DOI: 10.1371/journal.pone.0062781
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean Diet, Telomere Maintenance and Health Status among Elderly

Abstract: Leukocyte telomere length (LTL) and rate of telomere shortening are known biomarkers of aging while, numerous studies showed that Mediterranean diet (MD) may boost longevity. We studied association between telomere length, telomerase activity and different adherence to MD and its effects on healthy status. The study was conducted in 217 elderly subjects stratified according Mediterranean diet score (MDS) in low adherence (MDS≤3), medium adherence (MDS 4–5) and high adherence (MDS≥6) groups. LTL was measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
127
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(138 citation statements)
references
References 32 publications
(46 reference statements)
6
127
0
5
Order By: Relevance
“…La adhesión a patrones dietéticos que incluyen un consumo elevado de una amplia variedad de alimentos vegetales y bajo consumo de alimentos altamente procesados, como la dieta mediterránea, parece ser la forma más evidente de prevenir el desgaste de los telómeros (42,46,152,167). Cabe señalar que solo tres de los estudios con resultados significativos en relación con la asociación entre los patrones dietéticos y TL evaluaron la calidad de la dieta (147,156,164).…”
Section: Resultados Y Discusiónunclassified
See 2 more Smart Citations
“…La adhesión a patrones dietéticos que incluyen un consumo elevado de una amplia variedad de alimentos vegetales y bajo consumo de alimentos altamente procesados, como la dieta mediterránea, parece ser la forma más evidente de prevenir el desgaste de los telómeros (42,46,152,167). Cabe señalar que solo tres de los estudios con resultados significativos en relación con la asociación entre los patrones dietéticos y TL evaluaron la calidad de la dieta (147,156,164).…”
Section: Resultados Y Discusiónunclassified
“…Sin embargo, no se estudió su efecto en otra cohorte de edad que no fuera en población joven. En uno de los estudios transversales, tal y como el autor sugiere, puede haber un sesgo de supervivencia puesto que la muestra de población utilizada presentaba una edad de 77 años, que es superior al lími-te de edad para obtener una evaluación fiable de la TL (46). Por ello, puede suceder que tanto este sesgo de supervivencia como el uso de una población específica conlleven que la asociación con la longitud de los telómeros no sea fiable y por consiguiente, tampoco generalizable a otros grupos.…”
Section: Resultados Y Discusiónunclassified
See 1 more Smart Citation
“…To date, only two studies have investigated the relationship between MeDi and LTL in human populations. In one study of elderly (mean age of 77 years) subjects, high adherence to a MeDi was associated with longer LTL and higher telomerase activity (Boccardi et al 2013). In another study of a US cohort of middle-aged women, higher Alternate Mediterranean Diet scores were associated with higher age-adjusted mean LTL.…”
Section: Introductionmentioning
confidence: 98%
“…The hypothesis originally motivating many of these studies was that shorter telomeres would be associated with an increase in cancer risk, because LTL has been found to be inversely related to a number of cancer risk factors, including age, smoking, diabetes, hyperinsulinemia, low-grade chronic inflammation, and exposure to environmental air pollution (15)(16)(17). The results of epidemiologic studies have been inconsistent, however, and suggested positive, negative, or null associations (12).…”
Section: Introductionmentioning
confidence: 99%